2011
DOI: 10.1007/s00508-011-0106-9
|View full text |Cite
|
Sign up to set email alerts
|

Das Fetale Tabaksyndrom – Ein Statement der Österreichischen Gesellschaften für Allgemein- und Familienmedizin (ÖGAM), Gynäkologie und Geburtshilfe (ÖGGG), Hygiene, Mikrobiologie und Präventivmedizin (ÖGHMP), Kinder- und Jugendheilkunde (ÖGKJ) sowie Pneumologie (ÖGP)

Abstract: Over more than 50 years, the nocuous effects of smoking in pregnancy on the fetus are well known. In the first years of science the focus was primarily on restricted fetal growth while in more recent years over 10.000 studies investigated the incomparably big sum of detrimental effects for the unborn's health. In this statement we want to present the recent scientific findings on this topic. The statement is aimed to show all doctors who treat pregnant women the present situation and evidence. In the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 186 publications
(170 reference statements)
0
6
0
1
Order By: Relevance
“…The most recent data in Austria—derived from 2010—show that 20–30 % of pregnant women smoked [ 10 ]. However, the rates registered in the present study were consistently lower than 20 %.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most recent data in Austria—derived from 2010—show that 20–30 % of pregnant women smoked [ 10 ]. However, the rates registered in the present study were consistently lower than 20 %.…”
Section: Discussionmentioning
confidence: 99%
“…A study comprising data from six European countries (Belgium, Bulgaria, Germany, Greece, Ireland, and Portugal) showed that the prevalence of smoking at the time of delivery varied between 7 % (Bulgaria) and 52.5 % (Ireland), with a mean smoking prevalence of 19.6 % [ 8 ]. Twenty-one percent of pregnant women smoked in Germany [ 18 ], while 20–30 % of pregnant women smoked in Austria in 2010 [ 10 ]. A study conducted in Spain in 2013, addressing the effects of smoking on fetal biometry, comprised 2478 women and revealed an overall smoking prevalence of 32 % [ 4 ].…”
Section: Smoking During Pregnancy In Europe and Austriamentioning
confidence: 99%
See 2 more Smart Citations
“…Neben den bekannten müt-terlichen Folgen nehmen die Risiken sowohl für Plazentadysfunktion, Früh-geburtlichkeit, Totgeburt, fetale Wachstumsretardierung, aber auch plötzli-chen Kindstod, jugendliche Adipositas, Asthma bronchiale und kardiovaskuläre Erkrankungen des Kindes zu. Dies führ-te zur Etablierung des Begriffs "fetales Tabaksyndrom" [15]. Im Rahmen der präkonzeptionellen Beratung sollte der Kinderwunsch als Motivation zur Nikotinkarenz dienen und entsprechende Angebote der Kassen, die ja auch im DMP vorgesehen sind, unterbreitet werden.…”
Section: Nikotin Alkoholunclassified